Characterization of Performance Acoustic Sandwich Composite With a Core of Polyurethane Foam-Agave Sisalana Fiber Reinforced Polyester for Noise Absorption - Ferriawan Yudhanto, Andika Wisnujati, Iwan Yahya (Jurnal Teknologi IST Akprind, 2015)
Absorber material has characteristic of acoustic that reflect and absorb sound wave. Absorption by porous material is very useful to reduce the sound power level that occurs so as to reduce the noise in the room. The sound absorbtion coefficient of the Acoustic Sandwich Composite (ASC) was determined by a two-microphone impedance measurement according to international standard ASTM 1050-98. Dimension of The ASC consist of 1 core and 2 skin with diameter 100 mm. Skin on front side designed has 5 hole (d=10 mm) and used 4 different thickness of polyurethane foam (PU-Foam) that is 10, 20, 30 and 40 mm used as core of ASC. The skin on both sides of sandwich composite made from continuous and chopped agave sisalana fibre reinforced polyester with thickness 5 mm. Value of Noise Absorption Coefficient (NAC) is given from 0 to 1, which means sound absorption is none in value 0, and sound absorption reaches the maximum in value 1 on frequency range 0 Hz -1.6 kHz. This case, it is shown on the foam with thickness 30 mm is good in the low frequency range with the higest value of NAC is 0,46. The ASC designed of thickness 30 mm foam core can raise reach value of the NAC in the low frequency (400 Hz-1000 Hz), highest value 0.80 at frequency 800 Hz. The ASC of thickness 10 mm foam core to be optimum for middle frequency (1000 Hz-1600), highest value 0.89 at frequency 1200 Hz.